Hyperbaric Oxygen Therapy Represses the Warburg Effect and Epithelial–Mesenchymal Transition in Hypoxic NSCLC Cells via the HIF-1α/PFKP Axis - Zhang, Linling; Ke, Jingjing; Min, Shengping; Wu, Nan; Liu, Fei; Qu, Zhen; Li, Wei; Wang, Hongtao; Qian, Zhongqing; Wang, Xiaojing (Frontiers in Oncology, 2021)
Background: Tumor cells initiate hypoxia-induced mechanisms to fuel cell proliferation, invasion, and metastasis, largely mediated by low O2-responsive Hypoxia-Inducible Factor 1 Alpha (HIF-1α). Therefore, hyperbaric oxygen therapy (HBO) is now being studied in cancer patients, but its impact upon non-small-cell lung cancer (NSCLC) cell metabolism remains uncharacterized. Methods: We employed the NSCLC cell lines A549 and H1299 for in vitro studies. Glucose uptake, pyruvate, lactate, and adenosine triphosphate (ATP) assays were used to assess aerobic glycolysis (Warburg effect). A quantitative glycolytic flux model was used to analyze the flux contributions of HIF-1α-induced glucose metabolism genes. We used a Lewis lung carcinoma (LLC) murine model to measure lung tumorigenesis in C57BL/6J mice. Results: HBO suppressed hypoxia-induced HIF-1α expression and downstream HIF-1α signaling in NSCLC cells. One HIF-1α-induced glucose metabolism gene -- Phosphofructokinase, Platelet (PFKP) – most profoundly enhanced glycolytic flux under both low- and high-glucose conditions. HBO suppressed hypoxia-induced PFKP transactivation and gene expression via HIF-1α downregulation. HBO’s suppression of the Warburg effect, suppression of hyperproliferation, and suppression of epithelial-to-mesenchymal transition (EMT) in hypoxic NSCLC cell lines is mediated by the HIF-1α/PFKP axis. In vivo, HBO therapy inhibited murine LLC lung tumor growth in a Pfkp-dependent manner. Conclusions: HBO’s repression of the Warburg effect, repression of hyperproliferation, and repression of EMT in hypoxic NSCLC cells is dependent upon HIF-1α downregulation. HIF-1α’s target gene PFKP functions as a central mediator of HBO’s effects in hypoxic NSCLC cells and may represent a metabolic vulnerability in NSCLC tumors.